Time to Emergence of the Lyme Disease Pathogen in Habitats of the Northeastern U.S.A. - Dorothy Wallace; Michael Palace; Lucas Eli Price; Xun Shi (Insects)
Ticks carry a range of pathogens, the best known of which causes Lyme disease, prevalent in the northeastern United States. Emerging diseases do not yet consist of a wide range of Lyme diseases, raising the question of how long it takes for a newly introduced tick-borne disease to establish itself. The aim of this study was to address this question, with the agent of Lyme disease used as the test case. A prior process-based model of the Ixodes scapularis (Say 1821) life cycle and the transmission of Borrelia burgdorferi (Burgdorfer 1982) between this tick and its various hosts was used to predict the dynamics of disease introduction into a new area. The importance of temperature, infection probabilities, and tick host populations, relative to that of other factors, was established by a global sensitivity analysis using Latin hypercube sampling. The results of those samples were analyzed to determine the time to near-equilibrium. Eight locations in New Hampshire were chosen for high/low temperature, high/low mouse, and high/low deer values. Mammal abundance was estimated by relating the known mammal density from previous studies to a MaxEnt analysis output. The time required to reach Borrelia endemicity in the ticks of New Hampshire ranged from 8 to 20 years in regions where the tick population is viable, with a strong dependency on susceptible tick host populations.